Influence of Media on Germination and Vigour of Mesua ferrea Linn. - Bahar, Nawa; Singh, V. R. R. (Indian Forester, 2007)
The present study was carried out to find the effect/ Influence of media on germination. The seed was sown in different media such as top of paper (TP), between paper (BP), sand (S) and top of sand (TS). The maximum germination per cent and high vigour index was recorded in the top of paper (TP) medium. Being a large size seed, it gave good results in sand (S) and top of sand (TS) also. It is evident from the results that the germination value of seed has little differences in both the media such as top of paper (TP) and top of sand (TS). Sand it self also proved a good medium and inexpensive other than. So, it is recommended that sand is good medium for testing the seed of Mesua ferrea in controlled condition.